Biallelic CYP24A1 variants presenting during pregnancy: clinical and biochemical phenotypes. Issue 6 (June 2020) - Griffin, Tomás P; Joyce, Caroline M; Alkanderi, Sumaya; Blake, Liam M; O'Keeffe, Derek T; Bogdanet, Delia; Islam, Md Nahidul; Dennedy, Michael C; Gillan, John E; Morrison, John J; O'Brien, Timothy; Sayer, John A; et al.
Abstract : Introduction: Inactivating mutations in CYP24A1, encoding vitamin D-24-hydroxylase, can lead to an accumulation of active vitamin D metabolites and consequent hypercalcaemia. Patient (infantile and adult) presentation is varied and includes mild-severe hypercalcaemia, hypercalciuria, nephrocalcinosis and nephrolithiasis. This study aimed to characterize the clinical and biochemical phenotypes of a family with two CYP24A1 missense variants. Methods: The proband and seven family members underwent detailed clinical and biochemical evaluation. Laboratory measurements included serum calcium, intact parathyroid hormone (iPTH), vitamin D metabolites and urine calcium and creatinine. Results: The proband presented during the second trimester of a planned pregnancy with flu-like symptoms. Laboratory tests showed elevated adjusted calcium of 3.27 (upper reference limit (URL: 2.30) mmol/L), suppressed iPTH (<6 ng/L), elevated 25(OH)D (264 (URL: 55) nmol/L) and elevated 1, 25(OH)D (293 (URL: <280) pmol/L). Ionized calcium was 1.55 (URL: 1.28) mmol/L. Sanger sequencing revealed two heterozygous missense variants in the CYP24A1 : p.(Arg439Cys), R439C and p.(Trp275Arg), W275R. The proband's brother and sister had the same genotype. The brother had intermittent hypercalcaemia and hypervitaminosis D. Only the sister had a history of nephrolithiasis. The proband's daughter and two nephews were heterozygous for the R439C variant. The proband and her brother frequently had elevated 25(OH)D:24, 25(OH)2 D ratios (>50) during follow-up. Conclusions: W275R is a new pathogenic CYP24A1 mutation in compound heterozygotic form with R439C in this family.